Knowledge Mapping in the Field of Library and Information Science in Scopus-Indexed Q1 Library Science Journals, 2018-2022 - Kamalia, Salmah; ibrahim, Cecep; Chafit, Annisa; Azahra, Baiq Sabrina; Trimulyani, Ririn; Sadino, Syahrani Rachmawati; Qatrunnadine, Keyza Najla; Akbar, Bagas Kurnia; Kangko, Danang Dwijo (Revista Cubana de Información en Ciencias de la Salud, 2024)
Knowledge mapping has spread beyond library and information science journals and into other fields. To give current insights into scientific literature, it is necessary to study the development of library and information science research. The goal of this study is to examine trends in research subjects in the field of library and information science using keyword occurrences from 2018 to 2022. The research method employs a bibliometric approach, conducting knowledge mapping based on co-occurrence using the VOSviewer application. Data collection techniques involve downloading metadata from international scientific journals categorized under "Library and Information Science" and indexed as Q1 on the Scimago Journal Rank website. Based on the downloaded metadata, the ISSN is used to obtain the metadata of each journal in CSV format from the Scopus. The results of the research indicate that library science studies have expanded into the fields of technology and health, as evidenced by the high occurrence of keywords such as "human" with 1310 occurrences and "social networking" with 732 occurrences.